Infection by Zika virus and reproduction. When is the right time? - Espinosa-Barrero, Michael Steven (2019)
The Zika virus infection corresponds to one of the epidemics of great impact in the Americas defined as a public health emergency of international importance (ESPII) in 2016 by the WHO, characterized by a self-limited disease with sexual, vertical and by vectors transmission routes, of great impact in the tropics. Congenital malformations have been described in children of women who had infection during pregnancy that affect the central nervous system, as is the case of microcephaly, among other irreversible structural malformations, on the other hand, in adults after the end of the course during the clinical setting of the infection virus, RNA has been found up to 6 months later in some men, this proposes to identify possible risks in the transmission of the disease after the clinical setting is resolved and the fertilization and gestation in couples with a history of infection. The proposed recommendations in relation to the reproduction and prevention of sexual transmission of the ZIKV are based on epidemiological aspects and findings of different studies and case reports where it is taken into account finding of the virus in vaginal secretions and semen, data that they delimit a time for the right moment. In the case of men, they should wait for three to six months and women should wait around eight weeks to have sex for conceptual purposes. In addition, during pregnancy, barrier methods should be used to prevent the transmission of infection and a possible congenital syndrome.